Occult aesthetics : synchronization in sound film - Donnelly, K. J. (Kevin J.) (Oxford music/media series., 2013)
Donnelly focuses on an often overlooked aspect of audiovisual culture that is crucial to the medium's powerful illusions. This book examines the perceptual origins for audiovisual culture, as well as the technological basis of this psychological process. Concentrating on the connection between sound and image, it contends that attending to the musicality of film soundtracks can unlock the veiled 'occult' psychology invoked by the hidden marriage of the two.